Effect of Quinolones on Sperm Count and Motility in Male Albino Rats (Medical Forum Monthly, 2024)
Objective: To determine the effects of quinolones on sperm count and motility in male albino rats.Study Design: Experimental studyPlace and Duration of Study: This study was conducted at the Pharmacology Department of Post Graduate Medical Institute, Lahore for the total duration of 84 days from May 2011 to July 211.Materials and Methods: Eighty male albino rats were randomly divided into A,B, C and D groups each group having 20 albino rats. These groups were further subdivided into A1, A2, B1, B2, C1, C2, D1 and D2 having 10 albino rats in each group. Ciprofloxcin, ofloxacin and enoxacin dissolved in distilled water were given at 135mg/kg/day, 72mg/kg/day and 12.5mg/kg/day to groups A, B & C respectively for 12 weeks. Distilled water was given to group D being a control group for the same time period. The animals in subgroups Al, B1, Cl and D1 were sacrificed on 42nd day and samples were taken from epididymus. The caudal epididymus was dissected out and very small incision was made in the caudal epididymus. Seminal fluid was then squeezed on to the microscope slide. Epididymal sperms were assessed by calculating motile spermatozoa per unit area and expressed as percent motility. Epididymal sperm count were made by using haemocytometer and were expressed as million per ml of suspension.Rats in subgroup A2, B2, C2 and D2 were kept alive till 84th day after stopping drugs at 42nd day to find out if there was any reversible change in sperm count and motility after discontinuation of the treatment.Results: Significant decrease in sperm count motility was observed as compared to the Control group. It was further noted that the values did not return back to normal even after the discontinuation of the treatment.Conclusion: Quinolones reducesperm count and motility and should be used carefully for long term therapy.